Holistyczne podstawy rozwoju teorii logistyki wojskowej - Brzeziński Marian H. (2024)
The paper presents the following research problem: whether the adoption of holism as a philosophical concept can be the foundation for developing the theory and development of military logistics. It was hypothesized that the reason for the slow development of the theory of military logistics is the authors' less interest in formalized logic on the basis of which theoretical logistics can be developed. The research presented in the article fills the research gap in the search for the foundations of logistics theory in a holistic approach. A holistic approach to military logistics was analyzed as the basis for the development of the theory of military logistics. A systemic approach derived from holism was characterized. teleology, processualism and praxeology. It was found that military logistics occurs most often as a scientific specialty in the following sciences: safety, management and quality, and engineering and technical sciences. It was determined that the subject of research in logistics are logistics systems and the processes implemented within them and that it does not have a sufficiently developed cognitive and methodological apparatus. The relationship between systems theory and military logistics was presented, and military logistic systems and their features and functioning were characterized. As a result of the research, the following conclusion was formulated: holism and the systemic approach derived from it may constitute the basis for the development of theory and cognition in military logistics.